Critical survival periods in prostate cancer in Sweden explored by conditional survival analysis - Hemminki, Kari; Zitricky, Frantisek; Sundquist, Kristina; Sundquist, Jan; Försti, Asta; Hemminki, Akseli; Hemminki, Otto (Cancer medicine, 2024)
BACKROUND: We wanted to characterize conditional survival in prostate cancer (PC) in Sweden around and after 2005 when the vast increase in incidence due to the opportunistic testing for prostate specific antigen (PSA) culminated. We hypothesize that analyzing survival data during that time period may help interpret survival trends. We focus on stage-specific analysis using conditional survival in order to define the periods when deaths most commonly occurred. METHODS: Data on PC patients were obtained from the Swedish cancer registry for analysis of 1-, 2.5- and 5-year relative survival and conditional relative survival between years 2004 and 2018. Tumor-node-metastatic stage classification at diagnosis was used to specify survival. RESULTS: Small improvements were observed in stage- and age-related relative survival duriring the study period. Applying conditional relative survival showed that survival in stage T3 up to 2.5 years was better than survival between years 2.5 and 5. Survival in stage T4 was approximately equal in the first and the subsequent 2.5-year period. For M1, the first 2.5 year survival period was worse than the subsequent one. The proportion of high risk and M1 disease in old patients (80+ years) remained very high and their survival improved only modestly. CONCLUSIONS: The data indicate that M1 metastases kill more patients in the first 2.5 years than between years 2.5 and 5 after diagnosis; T4 deaths are equal in the two periods, and in T3 mortality in the first 2.5-year period is lower than between years 2.5 and 5 after diagnosis. Conditional survival could be applied to explore critical survival periods even past 5 years after diagnoses and to monitor success in novel diagnostic and treatment practices. Improvement of survival in elderly patients may require clinical input.
Keywords: analýza přežití; Male; Survival Rate; stage; Neoplasm Staging; Prostatic Neoplasms; Aged; mužské pohlaví; senioři; age; registrace; treatment; Survival Analysis; prostatický specifický antigen; prognosis; lidé; Humans; conditional relative survival; nádory prostaty; Sweden; Registries; staging nádorů; Prostate-Specific Antigen; míra přežití; Švédsko